Classification methods for ground deformation - Вовк, О.О.; Гай, А.Є.; Рябчевський, О.В. (Proceedings of National Aviation University (archive), 2007)
Classification for unsafety categories defining of different variants of earth-deformative processes according to factual measurements was adduced. Nomograms of earth failure classification depending on conditions of underground mining were developed.